Two new species of Enochrus Thomson, subgenus Hugoscottia Knisch, from Costa Rica and Mexico (Coleoptera: Hydrophilidae) - Short, A. E.z. (Zootaxa, 2005)
Two species of Enochrus Thomson, subgenus Hugoscottia Knisch, are described as new: Enochrus (Hugoscottia) plicatus, new species, from Jalisco State, Mexico and E. (H.). talamanca, new spe- cies, from Cartago Province, Costa Rica. This is the first report of Hugoscottia outside of South America. Photographs and remarks on the habitat of E. (H.) talamanca are provided. The male genitalia of both species are illustrated.El género Enochrus subgénero Hugoscottia, se registra por primera vez fuera de Sudamérica. Se describen dos especie nueva: Encochrus (Hugoscottia) plicatus, nueva especie, del Estado de Jalisco, México y E. (H.) talamanca, especie nueva, de la Provincia de Cartago, Costa Rica. Se proporcionan fotografías y notas del hábitat de E. (H.) talamanca. Se ilustra la genitalia masculina de las dos especies.